PERLINDUNGAN HUKUM TERHADAP JABATAN NOTARIS DALAM HAL MENJALANKAN AKTA PERDAMAIAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI JAYAPURA NOMOR: 261/Pid.B/2014/PN Jap) - ROZHI ANANDA SITEPU (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Muhd Yamin,SH, MS, CN2.  Dr. T. Keizerina Devi A, SH, CN, MHum3.  Notaris Syafnil Gani, SH, MHUm A dispute can occur between two or more parties, for one of them feels dissatisfied or harmed. In principle, the conflicting parties are given freedom to choose settlement mechanism. Indonesian administrative court system allows a dispute to be settled through alternative mechanism: Law No. 30/1999 on Arbitration and Alterative for Settling a Dispute. Article 1851 of the Civil Code states that settlement can be done for any case which is on going in the Court or the one which is being filed to the Court. There are two terms in the Reconciliation Deed: Acta van Dading and Acta van Vergelijk. A Notary’s Role in service sector is an official who is given an authority by the State to serve people in civil case, especially in drawing up authentic deeds. legal protection for notarial position in drawing up a reconciliation deed: Civil Liability, Administrative Liability, and Criminal Liability.Keywords: Legal Protection, Notary, Reconciliation Deed